Estimating window period blood donations for human immunodeficiency virus Type 1, hepatitis C virus, and hepatitis B virus by nucleic acid amplification testing in Southern Pakistan. Issue 6 (3rd January 2014) - Moiz, Bushra; Moatter, Tariq; Shaikh, Usman; Adil, Salman; Ali, Natasha; Mahar, Farheen; Shamsuddin, Naseem; Khurshid, Mohammad
<x xml:space="preserve">Abstract</x> Background Recently, strategic planning was initiated by the National Blood Transfusion Services Pakistan to improve its blood bank facilities. Emphasis has been placed on appropriate screening of blood products. Located in the southern region, Aga Khan University Hospital is a 700‐bed tertiary care academic institute with comprehensive blood banking. Screening of blood donors has been based on verbal screening and serologic testing to date. Additionally, the need of implementing nucleic acid testing (NAT) was considered in 2011 because of an upsurge in hepatitis epidemiology. The aim of this study was to analyze the efficacy of this additional donor screening program and to evaluate the impact of NAT on the yield and residual risk of transfusion‐transmissible viral infections. Study Design and Methods A total of 42, 830 blood donations collected between 2011 and 2012 were screened for routine serologic assays. Only serologically negative donors (n = 41, 304) were tested for NAT. The frequency of viral infections was evaluated through serologic techniques and NAT yield for viral agents was estimated for computing window period donors. Residual risk per million donors was computed for viral infections in seronegative blood donors. Results Serologic work‐up showed 1571 abnormal screening results in 1526 blood donors with the following results: hepatitis C virus antibodies (anti‐HCV; n = 708), hepatitis B surface antigen (n = 555), human immunodeficiency virus antibodies (anti‐HIV; n = 29), malaria (n = 30), VDRL (n = 249), and coinfection (n = 45). Thirty‐five NAT‐reactive samples were identified: HIV‐1, one; HCV, 27; and hepatitis B virus (HBV), seven. Incident rates per 105 donors were highest for HCV (453.3) followed by HBV (171.5) and HIV (72.2). Calculated residual risk per million donors was highest at 1 in 10, 900 for HBV, intermediate at 1 in 13, 900 for HCV, and least at 1 in 62, 600 for HIV. Conclusion Incidence rates and estimated residual risk indicate that the current risk of transfusion‐transmitted viral infections attributable to blood donation is relatively high in this country. The study recommends the parallel use of both serology and NAT screening of donated blood in countries that have high seroprevalence of these viral infections.